Migration and development in EU countries comparative analysis of approaches and projects - Nováková, Michaela; Klosová, Anna, 1942-; Jackson, Ian; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
The dissertation is focusing on migration in the EU, specifically on comparing Vietnamese communities in the Czech Republic and in France. The first and the second part of the dissertation is comparing these two Vietnamese communities. The historical background, migrants'integration to local community and position of immigrants at the Czech and French labour markets. The third part is assessing the impact of these communities on Vietnam.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]